1991
DOI: 10.1063/1.348659
|View full text |Cite
|
Sign up to set email alerts
|

A model for linewidth-dependent electromigration lifetime and its application to design rule scaling for narrow interconnects

Abstract: Analytical formulae for linewidth-dependent electromigration lifetime, as represented by a log-normal distribution, are derived based on a linewidth-independent log-normal grain size distribution. This formulation can quantitatively explain the experimentally observed increase of both the Median-time-to-failure and standard deviation (σ) as the linewidth decreases to become comparable to or less than the median grain size. Comparison between the theoretical prediction and experimental data for three metallizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…The variations in MTTF and DTTF with linewidth w (assumed equal to pd 0 [26]) are shown in figure 7. The dependence is as expected from several other studies [15,16,[18][19][20][21][22].…”
Section: Analysis Of Early Failuressupporting
confidence: 90%
See 2 more Smart Citations
“…The variations in MTTF and DTTF with linewidth w (assumed equal to pd 0 [26]) are shown in figure 7. The dependence is as expected from several other studies [15,16,[18][19][20][21][22].…”
Section: Analysis Of Early Failuressupporting
confidence: 90%
“…The failure-unit, or structural defect, model has received quite general usage in electromigration theory, and versions of it have been considered as descriptions for electromigration failure on many occasions (e.g. [9,[15][16][17][18][19][20][21][22]). The model was originally developed by Agarwala et al [17] to describe the behaviour of the failure distribution as a function of the line length, and it was later developed by Cho and Thompson [19] to include the important dependence on linewidth.…”
Section: Failure-unit Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In single crystal segments, surface diffusion is the dominant transport path, while in polycrystalline segments, grain boundary diffusion dominates transport. We quantify the proportion of the total line length of polycrystalline segments as the parameter p. This parameter was used to explain the effects of microstructure on Al interconnect mass transport [18]. However, Cu interconnects are fabricated through a damascene process.…”
Section: Modeling Of Drift Velocity For Polycrystalline Conductormentioning
confidence: 99%
“…Some researchers observed the failure time of polycrystalline lines to increase slowly with linewidth [3][4][5][6]. It was suggested that such lines be better described as serial/parallel combinations of failure elements [6].…”
Section: N Ineqs(2)and(3) Asmentioning
confidence: 99%